Role of Stressful Life Events, Avoidant Coping Styles, and Neuroticism in Online Game Addiction among College Students: A Moderated Mediation Model - Li, Huanhuan; Zou, Yingmin; Wang, Jiaqi; Yang, Xuelin (Frontiers in Psychology, 2016)
Online game addiction (OGA) is becoming a significant problem worldwide. The aim of this study was to explore the incidence of OGA and the roles of stressful life events, avoidant coping styles (ACSs), and neuroticism in OGA. A total of 651 Chinese college students were selected by random cluster sampling. Subjects completed the Chinese version of Young’s eight-item Internet Addiction Scale (CIAS), Online Game Cognition Addiction Scale (OGCAS), Revised Eysenck Personality Questionnaire Short Scale in Chinese (EPQ-RSC), Chinese College-student Stress Questionnaire, and Coping Style Questionnaire. Structural equation modeling (SEM) was used to explore the interactive effects of stressful life events, ACSs, and neuroticism on OGA. Of the 651 participants in the sample, 31 (4.8%) were identified as addicts. The incidence of OGA was two times higher for males than females. The addicts had markedly higher scores on the neuroticism subscale of the EPQ-RSC than non-addicts. Compared to non-addicts, addicts were more apt to use ACSs. Having an avoidant coping strategy mediated the effect of stressful life events on OGA. Furthermore, neuroticism moderated the indirect effect of stressful life events on OGA via ACSs. Applications of these findings to etiological research and clinical treatment programs are discussed.